Mengungkap Makna Puitik dalam Lagu Yā ‘Āsyiqah al-Ward Karya Zaki Nassif: Analisis Semiotika Michael Riffaterre - Bayu Ihsan Sauqi; Akmaliyah Akmaliya; Khomisah Khomisah (Dzil Majaz: Journal of Arabic Literature, 2026)
This study aims to uncover the mechanism of the shift in meaning from aesthetic romanticism to moral guidance in contemporary Arabic literary works. The main data source used in this study is specifically the lyric text of the song "Yā ‘Āsyiqah al-Ward" by Zaki Nassif, written in the fusha variety of Arabic. Using a descriptive qualitative method, this study applies the analytical knife of Michael Riffaterre's modern semiotic theory which includes the stages of heuristic-hermeneutic reading, the convention of indirect expression, and the search for matrices, models, and variants. The results show that the lyric text consistently demystifies the clichéd symbols of traditional romantic aesthetics. Romantic relationships are no longer seen as merely private expressions of affection, but are reconstructed by the text matrix into a space of ethical awareness that demands commitment, emotional honesty, and relational responsibility between humans. The academic contribution of this study is to enrich the study of contemporary popular Arabic literature by proving the rigidity and dynamism of Riffaterre's semiotic theory when operated on the medium of popular music texts. The implications of this research confirm that modern cultural texts are capable of resisting and creatively transforming classical poetic traditions (ghazals) without losing the depth of their ethical content and moral messages for society.